3D-printability of aqueous poly(ethylene oxide) gels. (November 2019) - Viidik, Laura; Seera, Dagmar; Antikainen, Osmo; Kogermann, Karin; Heinämäki, Jyrki; Laidmäe, Ivo
Graphical abstract: Model lattices were printed using extrusion-based 3D printing and various process parameters. The present lattices were compared with a theoretical ideal lattice to evaluate the 3D-printability of aqueous PEO gels. Highlights: PEO is an applicable material for extrusion-based 3D printing. Printing head speed and plate temperature influence 3D-printability the most. Extrusion-based printing does not induce solid-state changes in PEO. Abstract: Printing technologies combined with a computer-aided design (CAD) have found an increasing number of uses in pharmaceutical applications. In extrusion-based printing, the material is forced through a nozzle to form a three-dimensional (3D) structure pre-designed by CAD. The aim of this study was to evaluate the 3D-printability of biocompatible aqueous poly(ethylene oxide) (PEO) gels and to investigate the effects of three formulation parameters on the 3D printing process. The impact of PEO concentration (gel viscosity), printing head speed and printing plate temperature was investigated at three different levels using a full factorial experimental design. The aqueous PEO gels were printed with a bench-top extrusion-based 3D printing system at an ambient room temperature. The viscosity measurements confirmed that the aqueous PEO gels follow a shear-thinning behaviour suitable for extrusion-based printing. Heating the printing plate allowed the gel to dry faster resulting in more precise printing outcome. With the non-heated plate, the gel formed a dumbbell-shaped grid instead of straight lines. Higher concentration and more viscous PEO gels formed the best structured 3D-printed lattices. In conclusion, the accuracy and precision of extrusion-based 3D printing of aqueous PEO gels is highly dependent on the formulation (PEO concentration) and printing parameters (printing head speed, plate temperature). By optimizing these critical process parameters, PEO may be suitable for printing novel drug delivery systems.